#1
[tex] \tt \: 6(x + 2) - (4x - 14)[/tex]
- Distribute 6 through the parentheses
[tex] \tt6x + 12 - 4(4x - 14)[/tex]
- Distribute -4 through the parentheses
[tex] \tt6x + 12 - 16x + 56[/tex]
[tex] \tt - 10x + 68[/tex]
[tex]\rule{300pt}{3pt}[/tex]
#2
Let the two integers be x and x+2
ATQ,
[tex] \sf \: x + x + 2 = - 67[/tex]
Let's solve this !~
[tex] \sf \: 2x + 2 = - 67[/tex]
[tex] \sf \: 2x = - 67 - 2[/tex]
[tex] \sf \: 2x = - 69[/tex]
[tex] \sf \: x = - \frac{69}{2} [/tex]
[tex] \sf \: x = - 34.5[/tex]
[tex]\rule{300pt}{3pt}[/tex]
[tex]\large{|\underline{\mathtt{\red{N}\blue{u}\orange{m}\pink{b}\blue{e}\purple{r}\green{\:}\red{1}\blue{:}\orange{-}}}}[/tex]
[tex] \sf = \: x \\ \sf \: = - 34.5[/tex]
[tex]\large{|\underline{\mathtt{\red{N}\blue{u}\orange{m}\pink{b}\blue{e}\purple{r}\green{\:}\red{2}\blue{:}\orange{-}}}}[/tex]
[tex] \sf \: = x + 2 \\ \sf = - 34.5 + 2 \\ \sf \: = - 32.5[/tex]